Outcome in women with previous caesarean section in a secondary care hospital in rural South India - Dhanasekaran, Anuradha; Cherian, Anne George; Parveen, Aabidha; Emmanuel, Paul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Caesarean section has become increasingly the common method of delivery. From 1980 to 2001 the rate in UK has increased from 9% to 21% of all births. The aim of the study was to find out the outcome of delivery in women with previous cesarean section, the mode of delivery, maternal and fetal outcome of labour and various factors which influence the mode of delivery. Methods: 150 women with one previous caesarean section who attended the antenatal clinic and fit the inclusion criteria were enrolled in the study. Results: Success rate of VBAC was 30.5% among those included in trial of labour after caesarean section (TOLAC). 60.7% of the enrolled women underwent elective repeat caesarean section of which 54.9% were at the patients’ request. Favorable Bishop’s score (p= 0.0002) and previous cesarean section for breech (p=0.191) are positively associated with VBAC. Incidence of maternal complications in the study was 10.67% and 2.5% babies had an Apgar <7 at 5 minutes. There was no maternal or neonatal mortality. Conclusions: The VBAC rate in the study is 30.5% in carefully selected patients for trial of scar with the existing litigation pressure. TOLAC can be judiciously implemented in carefully chosen patients even in rural health setting equipped with required facilities. Patient’s participation in the decision making has brought down the VBAC rate which is reflected by the increased repeat elective cesarean section done at patients’ request (54.9%). Factors such as prior vaginal delivery, favorability of the cervix, indication of previous cesarean section, onset of labour and birth weight are highly significant in deciding the success of VBAC and can be used to improve VBAC rates in practice.